David E. Fishman, The Book Smugglers: Partisans, Poets, and the Race to Save Jewish Treasures from the Nazis (Lebanon, New Hampshire: ForeEdge / University Press of New England, 2017), 322 str. (Časopis za suvremenu povijest, 2020)
Prikaz knjige